Cognitive and Affective Factors that Influence the Purchase Intention of Live Consumers - Santoso, Sindi Puji; Nadila Tri Natasya; Siska Ernawati Fatimah (Institut Teknologi dan Bisnis Asia Malang, 2025)
Currently, most people like online shopping on various marketplace platforms. One of the platforms for online shopping through live shopping has its own uniqueness in the eyes of consumers who shop online. This study aims to analyze the purchase intention of live shopping for people in the city of Cirebon as seen from affective and cognitive. This study uses a quantitative approach and collects data through a questionnaire. This study has a population of people in the city of Cirebon aged 15-29 years, using the Slovin formula, and getting the number of respondents as many as 400. The data analysis method used is Structural Equation Modeling- Patrial Least Square (SEM-PLS). The research findings indicate that cognitive and affective linkages have a significant impact on purchase intention. This shows that both variables affect consumer purchase intention in Cirebon City. However, this purchase intention is more driven by effective where someone who is interested in buying through live shopping is dominated by emotions and feelings of likes and dislikes in product evaluation compared to information or knowledge that is remembered about the product.